TINJAUAN ATAS PARIWISATA DAN PERLINDUNGAN HUKUM DAFTAR BIDANG USAHA TERTUTUP TERBUKA UNTUK INVESTASI - Gokma Toni Parlindungan S; Erniwati Erniwati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The existence of tourism in an area can be said to be a complex phenomenon in society. Here there is an attraction between tourist areas that have an attraction, the community or local residents, and the tourists themselves. Each tourist area certainly has its own charm to be visited by tourists. The problem of the attractiveness of tourist destinations really depends on the tastes of the tourists themselves, so managers or the local community must indirectly try to meet the tastes of visitors so that tourism in their area can be well received and enjoyed by tourists. The existence of trade both nationally and internationally ultimately encourages the growth of industries such as hotels, recreation areas and culinary tourism, of course. This is the main activity of regional tourism development. Not only culture is being sold, but also local wisdom and regional uniqueness. Modern tourism destinations are very complex and very capitalistic, thus modern tourism management must use accurate and measurable business management. The objective of organizing investment can only be achieved if the supporting factors hindering the investment climate can be overcome, among others by improving coordination between central and regional government agencies, creating an efficient bureaucracy, legal certainty in the investment sector, highly competitive economic costs, and a conducive business climate in the field of employment and business security. Determination of business fields, both closed and open for investment purposes has a very important meaning in the framework of investment in Indonesia. Keywords: Tourism, Legal Protection, Investment.